(untitled) (Revista da Faculdade de Odontologia - UPF, 2014)
Focal Epithelial Hyperplasia (FEH) or Heck’s disease is a rare and benign condition characterized by cell proliferation in the squamous epithelium, which is manifested clinically as verrucous projections. It is associated with Human Papillomavirus (HPV) subtype 13 or 32, and it is often observed in children, young adults, and middle aged individuals, as well as some ethnic groups such as Indians and Eskimos, which suggests a possible hereditary influence. Objective: knowing that FEH is a rare disease among the Brazilian population, this article reports a case of FEH in a Brazilian family. Case report: a 27 year-old woman was assisted in the Department of Dentistry of the Federal University of Rio Grande do Norte (UFRN) showing round, plane, and well-defined lesions localized in the oral cavity, with an evolution of six years. Lesions underwent incisional biopsy, and the microscopic analysis revealed epithelial changes such as epithelium hyperplasia and prominent acanthosis. These histopathologic findings were consistent with the clinical hypothesis of FEH. Final considerations: this report reinforces the need for an accurate clinical assessment, so dentists are able to recognize, diagnose, and treat FEH in their own patients.